2009
DOI: 10.1111/j.1365-2133.2009.09160.x
|View full text |Cite
|
Sign up to set email alerts
|

Warts in primary schoolchildren: prevalence and relation with environmental factors

Abstract: One-third of primary schoolchildren have warts. This study does not find support for generally accepted wart prevention recommendations, such as wearing protective footwear in communal showers and swimming pool changing areas. Rather, recommendations should focus on ways to limit the transmission of wart viruses within families and school classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 13 publications
11
104
1
9
Order By: Relevance
“…Coming from a large family was associated with an increased risk of contracting warts, although this was not statistically significant. Similar findings have been reported by other studies [19], as well as an increased risk for children living in lower social classes [19,22]. In large families and in families of low social class, overcrowding and poor personal hygiene, as well as sharing clothing, may play a role in the transmission of such infectious skin diseases [19].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Coming from a large family was associated with an increased risk of contracting warts, although this was not statistically significant. Similar findings have been reported by other studies [19], as well as an increased risk for children living in lower social classes [19,22]. In large families and in families of low social class, overcrowding and poor personal hygiene, as well as sharing clothing, may play a role in the transmission of such infectious skin diseases [19].…”
Section: Discussionsupporting
confidence: 88%
“…A large cross-sectional study involving 1,465 primary school children from four Dutch primary schools aged 4-12 years found no effect of visiting swimming pools on the risk of warts. The authors concluded that public showers or swimming pool visits were not related to the presence of warts [22]. In contrast with these findings, a recent study conducted in El-Dakahlia rural area, Egypt [25], reported a significant risk of developing warts to be associated with swimming in channels of the Nile River, with an adjusted OR of 5.6 (95% CI=2.9-10.6).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…12 En un estudio reciente realizado en nuestro país con niños que asistían a la escuela primaria se reveló una prevalencia del 10,9%. 13 Así cobran relevancia las medidas preventivas contra la transmisión del VPH.…”
Section: Discussionunclassified
“…Verrucae vulgaris, commonly referred to as common warts, have a high prevalence of 3%–13% in the general population and up to 33% in primary school children 1, 2, 3, 4, 5…”
Section: Short Reportmentioning
confidence: 99%